Exploring the hidden diversity among small yellow frogs of the Colombian Llanos (2024)
Increased extinction rates and reduction of home ranges present some of the major problems for biodiversity worldwide, especially for cryptic diversity, to which conservation efforts can not be directed. Traditional comparative morphology fails to distinguish cryptic species, leading to the implementation of integrative taxonomy which not only uses morphology, but also genetic and ecological data to delimit new species. The Hylidae family of anurans is a prime candidate for studies in cryptic diversity, especially in the foothills of the Andean mountain range. Given morphological similarities and geographical closeness, cryptic species among Dendropsophus minutus, Dendropsophus stingi and Dendropsophus mathiassoni will be assessed through integrative taxonomy. Molecular data showed that the description of D. stingi did not result in a taxonomic over-split and despite the diagnostic trait being able to differentiate D. stingi from D. minutus, its field implementation may not be very effective at that moment. DNA sequences also indicate a high level of cryptic species among the D. minutus species group.